Dataset Unveiling the Landscape: A Deep Dive into Online Business and Tax Evasion Literature - Lestari, Melati Indah; Multazam, Mochammad Tanzil; Pristiwanto, Pristiwanto (Proceedings of The ICECRS, 2023)
This data article describes a comprehensive analysis of literature related to "Online Business and Tax Evasion" sourced from the Lens.org database. Using keyword-based searches and filtering techniques, data was exported and inputted into the Zenodo.org database for research purposes. The analysis unveils patterns in the publication, such as the leading institutions contributing to this field, fluctuating publication rates over the years, dominant fields of study, and the most active authors and publishers. The data not only offers insights into the landscape of research on online business and tax evasion but also serves as a valuable resource for scholars and the general public. Highlights: The United Kingdom emerges as the most active country, contributing 61 articles, with leading institutions like LSE and Teeside University at the forefront. Publication trends observed from 1997 to 2021 indicate fluctuations, with 2018 seeing the highest number of articles at 28. The top fields delving into this topic are political science, law, business, economics, and sociology, demonstrating the interdisciplinary nature of the subject. Keywords: Online Business, Tax Evasion, Lens.org, Literature Analysis, Research Trends